2009
DOI: 10.1080/02680510902879478
|View full text |Cite
|
Sign up to set email alerts
|

Tutors’ Forum: engaging distributed communities of practice

Abstract: The need to engage students studying at a distance in order to reduce isolation, foster a sense of belonging, and enhance learning has received significant attention over the past few years. Conversely, very little research has focused on teachers working in this type of environment. In fact, we argue, they appear to be the forgotten dimension in "communities" of distance learning. In this paper we identify some of the problems generated by teaching university subjects simultaneously across a network of campus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…Another knot was tied when the lecturer and tutor kept in contact via email communication. (Beaumont, Stirling & Percy (2009) report that despite the advances in technology, email is the major form of communication between tutors and lecturers).…”
Section: The Notion Of Knotworking In Providing Post-training Supportmentioning
confidence: 99%
“…Another knot was tied when the lecturer and tutor kept in contact via email communication. (Beaumont, Stirling & Percy (2009) report that despite the advances in technology, email is the major form of communication between tutors and lecturers).…”
Section: The Notion Of Knotworking In Providing Post-training Supportmentioning
confidence: 99%
“…Studies by Dixon et al (2008) and Beaumont et al (2009) suggest the success of collaborative exercises depends largely on the online instructor's effectiveness in communicating expectations. Studies by Beaudoin (2013) and Lee (2012) suggest that online discourse can present barriers to students' participation in discussions, which can inhibit students' interactions even when using synchronous technologies that emulate classroom learning (Lee, 2012;Nortvig, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of high-speed Internet connectivity, online skills and familiarity with technology, as well as technical difficulties, are common challenges for e-learning students (Beaumont et al, 2009;Cradduck, 2012;Guo et al, 2014;Higgins & Harreveld, 2013;Nortvig, 2013;Reiach et al, 2012). Previous studies have found that online students report feelings of isolation due to distance, the disjointed nature of these programs (Beaumont et al, 2009;Higgins & Harreveld, 2011) and inadequate online communication between instructors and students (Abrami, Bernard, Bures, Borokhovski, & Tamim, 2011;Skramstad et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations